Speculative Geographies and the Horizons of Performance Studies - Metzger, Sean (Nordic Theatre Studies, 2023)
This essay examines performance in relation to speculative geographies, a term suggesting the search for and/or creation of worlds at once underdetermined and subject to the imagination. These endeavors might be utopic in the sense of envisioning new social formations or dystopic in the sense of connoting the effects of resource extraction and financial speculation. Building on a speculative geography called the Chinese Atlantic (based on a book of that name), the essay proceeds to elaborate Chinese transnational circulations in the Nordic region with an emphasis on the Arctic. In this vein, the Chinese Arctic is offered as another speculative geography that brings into focus emergent relationalities: between individuals, between nation-states, between human and non-human actants. These relationalities create the potential for social transformation at various scales with both life affirming and life negating effects. Divided into six parts, the essay provides a survey on which to scaffold future research. The first part explains the genealogy of the analytical frame it offers and indicates how the writing in terms of both style and content is meant to function. The second situates speculative geographies in relation to selected writings on utopias. The third highlights selected performances that might serve as an antecedent to a Chinese Arctic paradigm. The fourth continues this move with an emphasis on Chinese investment in the energy and transportation sectors of Nordic countries as well as some of the soft power moves to support these efforts. The fifth section discusses the implications of speculative geographies as hyperobjects. The conclusion returns to events that generated the article and the implications for utopic thinking.